1991
DOI: 10.1177/074391569101000203
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Advertising Claims: A Preliminary Investigation

Abstract: As organizations increasingly target consumers who are concerned about the environment, the nature of their advertising becomes more of an issue. While much has been written about the problems associated with environmental advertising, this phenomenon has seldom been addressed systematically. This paper is intended to ascertain the extent to which environmental ads contain misleading and deceptive claims and to pose public policy recommendations concerning environmental advertising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(111 citation statements)
references
References 2 publications
2
103
0
6
Order By: Relevance
“…The poor confidence in the SEE aspects of pro-socially positioned goods displayed by consumers is not surprising since some academic studies have found that many advertising campaigns in the past have been misleading with regards to the pro-social claims made (e.g. Kangun et al, 1991;Polonsky et al, 1998). This should be a concern for marketers in any industry as confidence has been argued to influence outcomes in a multitude of consumer contexts such as financial services (Llewelyn, 2005), food consumption (de Jonge et al, 2004;Squires et al, 2001), and clothing/fashion purchases (O'Cass, 2004).…”
Section: Trust In Srimentioning
confidence: 95%
“…The poor confidence in the SEE aspects of pro-socially positioned goods displayed by consumers is not surprising since some academic studies have found that many advertising campaigns in the past have been misleading with regards to the pro-social claims made (e.g. Kangun et al, 1991;Polonsky et al, 1998). This should be a concern for marketers in any industry as confidence has been argued to influence outcomes in a multitude of consumer contexts such as financial services (Llewelyn, 2005), food consumption (de Jonge et al, 2004;Squires et al, 2001), and clothing/fashion purchases (O'Cass, 2004).…”
Section: Trust In Srimentioning
confidence: 95%
“…However, the marketing literature has yet to examine the barriers facing consumers. The negative effects of greenwashing, and the general lack of trust felt by consumers toward green firms has been noted as an obstacle that many firms must attempt to overcome (Kangum et al 1991). In addition, a lack of green credibility, along with consumer cynicism and confusion, are issues associated with green marketing strategies (Carlson et al 1993;Davis 1993).…”
Section: Green Alliancesmentioning
confidence: 97%
“…Some researchers point out that emotional and simple messages are more effective in persuading individuals to buy or change their beliefs based on the assumptions that consumers often seek to minimize their cognitive effort, have limited ability, and a low threshold for boredom (Anderson and Jolson 1980;Shuptrine and McVicker 1981). Others, however, point out that environmental messages should not be treated in the same way as other product attributes, and that more specific, detailed, and informative claims are required to avoid misleading messages (e.g., Davis 1993Davis , 1994Kangun et al 1991). Given the increased effort required to process more complex messages, some researchers have found evidence that complex messages can positively affect attitude formation and memory (Steward and Koslow 1989;Phillips 1997;Lowrey 1998).…”
Section: Introductionmentioning
confidence: 92%
“…Third, environmental attributes are difficult to evaluate in that they are difficult to experience directly and are not easily evaluated either before or after purchase. Finally, environmental messages, such as 'earth friendly', 'green', 'recyclable', for example, are commonly evaluated by individuals with skepticism as incomplete, misleading, or greenwashing (Kangun et al 1991;Carlson et al 1993;Polonsky et al 1998;Ozanne and Vlosky 1997).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation